(3HZjI GdCQjH aj GNJUGQ GdJgPjH aj HjGf CSeGA GdQLGds - (3YeGO GdOjf ESeGYjd GHf eMeO Hf HQOS Hf fUQ HQOS Hf QSdGf GdHYdj CHh GdaOGA YeGO GdOjf GdHYdHcis; (3GdMGaX GdeRj , jhSa Hf YHO GdQMef Hf jhSa LeGd GdOjf GdRcj CHh eMeO GdbVGYj GdcdHj, LeGd GdOjf CHh GdMLGL GdMGaX GdeRj,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdYdeGA ai GdCeI cGdfLhe s
(3BNQgG (B:s
(3Ce SdeI RhL GdfHi (B((3U(B) s
(3de jMPa GdeDda QLGd GdJgPjH CMOkG hEfeG MPa HYV CfSGH GdeTghQjf hHYV fSH UGMH GdJQLeI hHPcQ GdLQM hGdJYOjd eNJUQkG HMPa GdSfOs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B236 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B308s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B47 s
Keywords: (3GdJGQjNs